Gimnasia neurocerebral para el desarrollo didáctico de niños de 4 a 5 años del nivel de Educación Inicial de la Escuela Isidro Ayora - Chanatasig Quimbita, Amanda Noemi (2023)
he present investigation was framed in the study of neurocerebral gymnastics for the didactic development of children from 4 to 5 years of age, taking into consideration that the development of cognitive abilities and functions is a transcendental element so that infants can correctly develop the process of learning. learning. However, it was considered that currently these strategies are not used in the context of Initial Education. The objective of the research was to stimulate cognitive development through neurocerebral gymnastics in boys and girls from 4 to 5 years of the Initial Education level of the Isidro Ayora School. The methodology applied for it, had a mixed approach with the application of the deductive, bibliographical, historical and dialectical method.